Dural tear post mastoidectomy repaired with Dura Gen - Wong, CY; Mohamed, Khairi; Awang, Mohamed Saufi; Mohamed, Irfan (Malaysian Medical Associations, 2010)
Dural exposure may occur during the course of thinning the tegmen tympani and tegmen mastoideum in mastoid procedure. If large area of dura is exposed or lacerated, cerebrospinal fluid and brain herniation may enter the mastoid cavity. We report a case of a patient with injured dura mater and tegmen mastoideum during mastoidectomy for chronic suppurative otitis media with cholesteatoma managed by DuraGen. The dura mater and tegmen defect healed totally showing the success of the procedure.A collagen matrix like DuraGen is an option for repairing dural tear in mastoid region.